Sense of coherence and coping styles in people with colostomy for colorectal cancer - Kurowska, Krystyna; Bartoszek, Magdalena (Contemporary Oncology/Współczesna Onkologia, 2008)
Sense of coherence (SOC) is a factor influencing the ability to cope with stress. The aim of the study was to estimate the level of SOC and coping styles in people with colostomy for colorectal cancer. The study included 47 people who took part in a periodic meeting of POL-ILKO – Polish Ostomy Association in Voivodship Hospital, Bydgoszcz. SOC was assessed using the SOC-29 questionnaire and the level of coping was measured using the Coping Inventory of Stressful Situations (CISS questionnaire). The study shows that the following factors influence the SOC and styles of coping: living conditions, social contacts and roles and functions in the family. Patients with higher comprehensibility and general SOC levels rarely apply task- and emotion-oriented styles of coping.